Manufacturing method of degradable food packaging paper
By adding cationic starch, wetting agent and composite sunscreen to food packaging paper and applying composite coatings to the surface to form a cross-linked structure, the existing packaging paper has been solved, and the high performance and degradability of food packaging paper suitable for light-proofing and preserving preservation is achieved.
Patent Information
- Application Number
- CN202510198434.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-22
- Publication Date
- 2025-04-25
AI Technical Summary
The existing biodegradable food packaging paper has shortcomings in waterproof and oil-proof performance and light-shielding and light-absorbing functions, and it is difficult to meet the food packaging needs that need to be preserved from light.
By adding cationic starch, wetting agent and composite sunscreen to the base paper and applying composite coating to the surface, a cross-linked structure is formed to improve waterproof and oil-proof performance, and at the same time, the light-shielding and light-absorbing effect is achieved using carbon black, zinc oxide and titanium dioxide in the composite sunscreen.
It achieves good waterproof and oil-proof performance and light-shielding effect of food packaging paper, and is suitable for food packaging that needs to be preserved from light. It has good degradability overall and reduces environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food packaging paper preparation, and in particular to a method for preparing degradable food packaging paper. Background Art
[0002] In order to achieve good waterproof and oil-proof isolation effects, traditional food packaging paper usually coats a layer of isolation material, such as polyethylene (PE), on the surface of the paper. However, although this practice improves the isolation performance of the packaging paper, it also brings serious environmental problems. Since materials such as PE are difficult to degrade, packaging paper containing these coatings cannot be completely decomposed in the natural environment, which is easy to cause environmental pollution, especially pollution to soil and water bodies. In addition, these non-degradable coatings also increase the difficulty of recycling and disposal, which is not in line with the current concept of sustainable development.
[0003] Based on the above situation, in the prior art, in order to solve the environmental problems of traditional food packaging paper, the patent with application number CN201911353170.7 proposes a degradable food packaging paper, the raw materials of which mainly include coniferous unbleached chemical wood pulp, broadleaf unbleached chemical wood pulp and nanocellulose fibrils, and the paper is prepared by specific pulping, pulping and papermaking processes. The patent also designs a surface glue, which is composed of hydrophobic nanocellulose and enzymatically treated cassava starch, and forms an emulsion-like glue through homogenization, and applies glue on the surface of the paper to improve its insulation performance. This kind of packaging paper achieves complete degradation while maintaining certain insulation performance, reducing the impact on the environment.
[0004] Although the above-mentioned degradable food packaging paper has made significant progress in environmental protection, there are still some shortcomings in practical applications. First, the surface rubber lacks a complex cross-linking structure, which leads to the unsatisfactory waterproof and oil-proof performance of the packaging paper. Secondly, the packaging paper does not have light-shielding and light-absorbing functions and cannot effectively block light, which limits its application in the packaging of foods that need to be kept away from light (such as certain foods rich in oil or pigments). Summary of the invention
[0005] In view of the technical defects existing in the background technology, the present invention proposes a method for making degradable food packaging paper, which solves the above technical problems and meets the actual needs. The specific technical solution is as follows: A method for making degradable food packaging paper comprises the following steps: S1, refining, refining coniferous wood pulp and hardwood wood pulp respectively, the beating degree of coniferous wood pulp after refining is 45-55°SR, and the beating degree of hardwood wood pulp is 35-45°SR, and then pulping is performed according to 65-75% coniferous wood pulp and 35-25% hardwood wood pulp to obtain mixed wood pulp; S2, adding cationic starch, a wetting agent, and a composite sunscreen agent to the mixed wood pulp in sequence, and then stirring and mixing them evenly; S3, adding water to the mixed wood pulp and diluting the mixed pulp to a concentration of 0.8% to 1.0%, using a fourdrinier paper machine to form the diluted pulp and obtain a wet paper sheet, with a papermaking machine speed of 350 to 450 m / min; S4, dehydrating the formed wet paper sheet by suction under a vacuum condition of 0.07-0.8 MPa, drying the wet paper sheet at a temperature of 80-90° C. for 8-10 minutes, and finally calendering the wet paper sheet on a calender to obtain a base paper; S5, preparing a composite coating, coating the composite coating on both sides of the base paper to form a composite coating, wherein the coating amount of the composite coating is 2 to 5 gsm; S6, heating at 100-120° C. for 5-10 minutes to solidify the composite coating on the base paper, thereby obtaining the degradable food packaging paper.
[0006] As a further technical solution of the present invention, in step S2, the added amounts (absolute dry weight) of the cationic starch, wetting agent and composite sunscreen are respectively: 1.0-1.2% cationic starch, 0.5-1.0% wetting agent and 1-5% composite sunscreen.
[0007] As a further technical solution of the present invention, the cationic starch is selected from any one of tertiary amine alkyl cationic starch and quaternary ammonium alkyl cationic starch, and the wetting agent is selected from any one of urea-formaldehyde resin and polyamide polyepichlorohydrin resin.
[0008] As a further technical solution of the present invention, the composite sunscreen agent includes the following raw materials: 60-70% carbon black, 20-15% zinc oxide, and 20-15% titanium dioxide. The particle size of the carbon black is 50-100 μm, the particle size of the zinc oxide is 150-400 μm, and the particle size of the titanium dioxide is 50-150 μm.
[0009] As a further technical solution of the present invention, in step S5, each component, measured by weight and fraction, comprises the following raw materials: 10 to 15 parts of modified activated carbon, 10 to 15 parts of modified chitosan, 20 to 25 parts of acrylic resin emulsion, 30 to 35 parts of polyethylene glycol, and 1 to 5 parts of initiator.
[0010] As a further technical solution of the present invention, in step S5, the preparation method of the composite coating is: take 35 parts of polyethylene glycol and put it into a heatable stirring device, heat it at 55°C to melt it, and then add 20 parts of acrylic resin emulsion, 10 parts of modified activated carbon, 10 parts of modified chitosan, and 1 part of initiator in sequence, stir and mix evenly to obtain a composite coating.
[0011] As a further technical solution of the present invention, in step S5, the molecular weight of the acrylic resin emulsion is 4000-6000, the polyethylene glycol is PEG-4000 with a molecular weight of 3600-4400, and the initiator is selected from any one of benzoyl peroxide and tert-butyl peroxide 2-ethylhexyl.
[0012] As a further technical solution of the present invention, in step S5, the preparation method of the modified activated carbon is: weigh 5.0g of activated carbon and 12g of KMnO4, put them into a 500mL beaker, and add 20mL of 10% H2SO4, then react at 35°C for 1h, filter, rinse the filter residue with a large amount of deionized water until neutral, and dry at 100°C to obtain activated activated carbon, add 2.0g of oxidized modified activated carbon and 4.0g of 3-bromo-1-propylene to 80mL of 60% ethanol solution, then stir and mix at 45°C in the dark for 12h, filter, wash with anhydrous ethanol, and dry at 50°C to obtain modified activated carbon.
[0013] As a further technical solution of the present invention, in step S5, the preparation method of the modified chitosan is: dissolve 1g of chitosan in 100mL of deionized water, adjust the pH to 5-7, slowly add aldehyde-polyethylene glycol-acrylate under stirring, react at 60°C for 3h, cool, filter, and dry under reduced pressure at 50°C to obtain modified chitosan.
[0014] As a further technical solution of the present invention, the mass ratio of the aldehyde-polyethylene glycol-acrylate to chitosan is: (1-1.5):1, the molecular weight of the aldehyde-polyethylene glycol-acrylate is 1000-2000, the molecular weight of the chitosan is 7000-8000, and the degree of deacylation is 75%.
[0015] The beneficial effects of the present invention are: The food packaging paper of the present invention has good degradability as a whole. The base paper of the packaging paper is mainly softwood pulp and hardwood pulp, both of which are natural renewable resources. The composite coatings coated on the surface of the base paper are all degradable materials, so that the entire packaging paper can be naturally degraded after being discarded, reducing environmental pollution. The base paper part of the present invention is pulped with softwood pulp and hardwood pulp, and cationic starch, a wetting agent and a composite sunscreen are added to effectively improve the strength, flexibility and sunscreen effect of the paper. The composite sunscreen can also be filled in the wood pulp fiber to further enhance the strength of the paper. The composite coating of the present invention is cross-linked by double bonds on acrylic resin, modified activated carbon and modified chitosan under the action of an initiator to form a dense cross-linked structure on the surface of the base paper, so that the food packaging paper has good waterproof and oil-proof properties. DETAILED DESCRIPTION
[0016] The implementation mode of the present invention is described below in conjunction with relevant embodiments. The implementation mode of the present invention is not limited to the following embodiments, and the present invention relates to relevant necessary components in the technical field, which should be regarded as the known technology in the technical field and can be known and mastered by the technical personnel in the technical field.
[0017] A method for making degradable food packaging paper comprises the following steps: S1, refining, refining coniferous wood pulp and hardwood wood pulp respectively, the beating degree of coniferous wood pulp after refining is 45-55°SR, and the beating degree of hardwood wood pulp is 35-45°SR, and then pulping is performed according to 65-75% coniferous wood pulp and 35-25% hardwood wood pulp to obtain mixed wood pulp; S2, adding cationic starch, a wetting agent, and a composite sunscreen agent to the mixed wood pulp in sequence, and then stirring and mixing them evenly; S3, adding water to the mixed wood pulp and diluting the mixed pulp to a concentration of 0.8% to 1.0%, using a fourdrinier paper machine to form the diluted pulp and obtain a wet paper sheet, with a papermaking machine speed of 350 to 450 m / min; S4, dehydrating the formed wet paper sheet by suction under a vacuum condition of 0.07-0.8 MPa, drying the wet paper sheet at a temperature of 80-90° C. for 8-10 minutes, and finally calendering the wet paper sheet on a calender to obtain a base paper; S5, preparing a composite coating, coating the composite coating on both sides of the base paper to form a composite coating, wherein the coating amount of the composite coating is 2 to 5 gsm; S6, heating at 100-120° C. for 5-10 minutes to solidify the composite coating on the base paper, thereby obtaining the degradable food packaging paper.
[0018] The entire preparation method of the present invention adopts degradable materials to ensure that the final product can be completely degraded in the natural environment, thereby reducing environmental pollution. When preparing the base paper, cationic starch, a wetting agent and a composite sunscreen are added to the base paper, and a composite coating is coated on the surface, thereby significantly improving the waterproof, oil-proof and insulating properties of the packaging paper. The introduction of modified activated carbon and modified chitosan in the composite coating further enhances the waterproof and oil-proof properties of the food packaging paper through the formation of a cross-linked structure. The carbon black, zinc oxide and titanium dioxide in the composite sunscreen effectively absorb and reflect light through a combination of different particle sizes, so that the packaging paper has a light-shielding and light-absorbing effect, and is suitable for foods that need to be stored away from light. By controlling the specific beating degree and ratio of coniferous wood pulp and broadleaf wood pulp, and optimizing parameters during papermaking and drying, the strength and uniformity of the paper are ensured, and the overall quality of the product is improved.
[0019] As one of the preferred embodiments of the present invention, in step S2, the added amounts (absolute dry weight) of the cationic starch, wetting agent, and composite sunscreen are respectively: 1.0-1.2% cationic starch, 0.5-1.0% wetting agent, and 1-5% composite sunscreen.
[0020] Furthermore, in the above scheme, the cationic starch is selected from any one of tertiary amine alkyl cationic starch and quaternary ammonium alkyl cationic starch, and the wetting agent is selected from any one of urea-formaldehyde resin and polyamide polyepichlorohydrin resin.
[0021] Specifically, the added amounts of cationic starch, wetting agent, and composite sunscreen are: 1.0% cationic starch, 0.5% wetting agent, and 1% composite sunscreen, respectively. The cationic starch is preferably tertiary amine alkyl cationic starch, and the wetting agent is preferably urea-formaldehyde resin.
[0022] The addition amount of cationic starch is 1.0% (absolute dry weight), and tertiary amine alkyl cationic starch is preferred. Tertiary amine alkyl cationic starch can form strong hydrogen bonds and ionic bonds with wood pulp fibers, thereby improving the dry strength and wet strength of the paper, and improving the surface smoothness and uniformity of the paper, making the base paper more suitable for coating.
[0023] The added amount of the wetting agent is 0.5% (absolute dry weight), and urea-formaldehyde resin is preferred. Urea-formaldehyde resin can adjust the moisture absorption and moisture release of paper, prevent the paper from deforming or breaking due to humidity changes, and improve the fiber structure inside the base paper, helping to make the base paper more flexible and durable.
[0024] The addition amount of the composite sunscreen is 1% (absolute dry weight). The composite sunscreen is composed of carbon black, zinc oxide and titanium dioxide. These ingredients have different particle sizes and optical properties, so they can play a light-shielding role in the base paper, making the food packaging paper suitable for packaging applications of foods that need to be kept away from light.
[0025] As one of the preferred embodiments of the present invention, the composite sunscreen agent includes the following raw materials: 60-70% carbon black, 20-15% zinc oxide, and 20-15% titanium dioxide. The particle size of the carbon black is 50-100 μm, the particle size of the zinc oxide is 150-400 μm, and the particle size of the titanium dioxide is 50-150 μm.
[0026] Specifically, the weight percentages of the components of the composite sunscreen agent are preferably: 60% carbon black, 20% zinc oxide, and 20% titanium dioxide. The particle size of the carbon black is preferably 50 μm, the particle size of the zinc oxide is preferably 300 μm, and the particle size of the titanium dioxide is preferably 150 μm.
[0027] Carbon black is a highly efficient light-absorbing material that can absorb visible light. Carbon black plays a dominant role in the composite sunscreen, giving full play to its light-absorbing properties, which can effectively reduce the light passing through the packaging paper, thereby protecting the food from the influence of light. Zinc oxide and titanium dioxide can reflect ultraviolet rays and part of the visible light. Titanium dioxide and zinc oxide together constitute the reflective layer of the composite sunscreen and cooperate with carbon black to ensure that the food packaging paper has a good light-shielding effect.
[0028] In addition, in the process of preparing base paper, carbon black, zinc oxide and titanium dioxide are filled between the wood pulp fibers of the mixed wood pulp in different particle sizes. Carbon black, with its smaller particle size, can penetrate into the gaps between fibers and enhance the light absorption properties of the paper. Zinc oxide and titanium dioxide, with their moderate particle size, form an effective reflective layer between the fibers to reflect part of the ultraviolet light and visible light. Carbon black, zinc oxide and titanium dioxide cooperate with each other with particles of different sizes, which not only improves the light-shielding effect of the paper, but also makes the internal structure of the base paper denser, enhances the strength and stability of the paper, and provides good structural strength and light-shielding protection for degradable food packaging paper.
[0029] As one of the preferred embodiments of the present invention, in step S5, each component, measured by weight and fraction, comprises the following raw materials: 10 to 15 parts of modified activated carbon, 10 to 15 parts of modified chitosan, 20 to 25 parts of acrylic resin emulsion, 30 to 35 parts of polyethylene glycol, and 1 to 5 parts of initiator.
[0030] Furthermore, in the above scheme, the preparation method of the composite coating is: take 35 parts of polyethylene glycol and put it into a heatable stirring device, heat it at 55°C to melt it, and then add 20 parts of acrylic resin emulsion, 10 parts of modified activated carbon, 10 parts of modified chitosan, and 1 part of initiator in sequence, stir and mix evenly to obtain a composite coating.
[0031] Specifically, among the above components, the modified activated carbon is treated by activated carbon oxidation to increase its surface hydroxyl groups, and reacts with 3-bromo-1-propylene to modify the carbon-carbon double bonds. The modified chitosan is treated by reacting chitosan with aldehyde-polyethylene glycol-acrylate to introduce a Schiff base structure and a carbon-carbon double bond with antibacterial properties. The acrylic resin emulsion is a film-forming component of the composite coating, which provides good adhesion and weather resistance. Polyethylene glycol is a film-forming component of the composite coating, which helps to mix and coat the coating components. The initiator is used to initiate cross-linking of double bonds on the acrylic resin, modified activated carbon and modified chitosan after coating.
[0032] In addition, after the activated carbon is oxidized, its internal void width increases, thereby increasing its adsorption performance. It can absorb excess moisture and oxygen and other gases in the packaging to a certain extent, slowing down the oxidation and spoilage process of the food and extending the shelf life of the food. At the same time, it works together with carbon black, zinc oxide and titanium dioxide in the packaging paper to effectively absorb and reflect light, increasing the light-shielding ability of the food packaging paper.
[0033] When preparing the composite coating, 35 parts of polyethylene glycol are placed in a heatable stirring device and heated at 55°C to melt to ensure that it is fully liquefied and easy to mix with other components. 20 parts of acrylic resin emulsion, 10 parts of modified activated carbon, 10 parts of modified chitosan and 1 part of initiator are added in sequence, stirring while adding to ensure that the components are evenly mixed. Stirring is continued until the coating presents a uniform, particle-free liquid state, that is, a composite coating is obtained. Then, the prepared composite coating is evenly coated on the surface of the base paper through a coating device. During the coating process, the components in the coating form a uniform film on the surface of the base paper. During the drying process after coating, the initiator induces a cross-linking reaction of the double bonds on the acrylic resin, modified activated carbon and modified chitosan at a temperature of 100°C to form a stable chemical bond connection, and the polyethylene glycol and other components are connected by hydrogen bonds, which enhances the cohesion and adhesion of the coating and the film-forming effect. The cross-linking reaction and the formation of hydrogen bonds form a complex and dense cross-linking structure inside the coating, which improves the waterproof, oil-proof and antibacterial properties of the coating.
[0034] As one of the preferred embodiments of the present invention, in step S5, the molecular weight of the acrylic resin emulsion is 4000-6000, the polyethylene glycol is PEG-4000 with a molecular weight of 3600-4400, and the initiator is selected from any one of benzoyl peroxide and tert-butyl peroxide 2-ethylhexyl.
[0035] Specifically, the molecular weight of the acrylic resin emulsion is preferably 4000, and the initiator is preferably benzoyl peroxide.
[0036] Acrylic resin emulsion is low molecular weight and has good fluidity. As the main film-forming substance, it can form a uniform and dense film on the surface of base paper. Its good fluidity helps to evenly coat the coating and ensure the consistency and smoothness of the coating.
[0037] The molecular weight of polyethylene glycol (PEG-4000) is 3600-4400, which belongs to the high molecular weight range. Polyethylene glycol is a film-forming component in the composite coating. Due to its high molecular weight characteristics, polyethylene glycol can reduce the water absorption of the composite coating after film formation and improve the waterproof performance of the coating. In addition, during the film formation process of the coating, polyethylene glycol and other components are connected in the form of hydrogen bonds, which enhances the cohesion and adhesion of the coating.
[0038] The initiator is preferably benzoyl peroxide. After the composite coating is coated on the surface of the base paper, the initiator triggers a cross-linking reaction of the double bonds on the acrylic resin, modified activated carbon and modified chitosan at a temperature of 100°C to form a stable chemical bond connection. The occurrence of the cross-linking reaction causes the coating to gradually solidify during the heating process to form a composite coating with good performance. By triggering the cross-linking reaction, the initiator helps to improve the strength, weather resistance and waterproof and oil-proof properties of the coating.
[0039] As one of the preferred embodiments of the present invention, in step S5, the preparation method of the modified activated carbon is: weigh 5.0g of activated carbon and 12g of KMnO4, put them into a 500mL beaker, and add 20mL of 10% H2SO4, then react at 35°C for 1h, filter, rinse the filter residue with a large amount of deionized water until neutral, and dry at 100°C to obtain activated activated carbon, add 2.0g of oxidized modified activated carbon and 4.0g of 3-bromo-1-propylene to 80mL of 60% ethanol solution, then stir and mix at 45°C in the dark for 12h, filter, wash with anhydrous ethanol, and dry at 50°C to obtain modified activated carbon.
[0040] In the preparation process of modified activated carbon, KMnO4 and dilute sulfuric acid solution are first used to oxidize the activated carbon. The purpose of this step is to increase the number of hydroxyl groups on the surface of the activated carbon through oxidation treatment, so as to provide active sites for the subsequent double bond modification reaction. After obtaining the activated activated carbon, the next step is to activate the activated carbon and modify the carbon-carbon double bonds on its surface. The specific steps are as follows: 2.0g of oxidized modified activated carbon and 4.0g of 3-bromo-1-propylene are added to 80mL of 60% ethanol solution. In this step, 3-bromo-1-propylene is used as a modifier, and the bromine group in its molecule can undergo a substitution reaction with the hydroxyl groups on the surface of the activated carbon, thereby introducing carbon-carbon double bonds into the surface of the activated carbon. The purpose of this step is to modify the carbon-carbon double bonds on the surface of the activated activated carbon, so as to provide reaction sites for the subsequent cross-linking reaction, thereby enhancing the performance of the composite coating.
[0041] As one of the preferred embodiments of the present invention, in step S5, the preparation method of the modified chitosan is: dissolve 1g of chitosan in 100mL of deionized water, adjust the pH to 5-7, slowly add aldehyde-polyethylene glycol-acrylate under stirring, react at 60°C for 3h, cool, filter, and dry under reduced pressure at 50°C to obtain modified chitosan.
[0042] Furthermore, in the above scheme, the mass ratio of the aldehyde-polyethylene glycol-acrylate to chitosan is: (1-1.5):1, the molecular weight of the aldehyde-polyethylene glycol-acrylate is 1000-2000, the molecular weight of the chitosan is 7000-8000, and the degree of deacylation is 75%.
[0043] Specifically, the mass ratio of aldehyde-polyethylene glycol-acrylate to chitosan is: (1.5):1.
[0044] When preparing modified chitosan, 1g chitosan was dissolved in 100mL deionized water, and then the pH of the solution was adjusted to 5-7. In the appropriate pH range, the amino group (-NH2) on the chitosan molecule can show good reactivity, which is conducive to condensation reaction with the aldehyde group. Under stirring, aldehyde-polyethylene glycol-acrylate was slowly added dropwise. Aldehyde-polyethylene glycol-acrylate is a compound containing aldehyde group, polyethylene glycol segment and acrylate group, and its molecular weight is controlled in the range of 1000-2000. Aldehyde group can condense with amino group on chitosan to form Schiff base structure, thereby introducing antibacterial properties. At the same time, acrylate group provides reaction site for subsequent cross-linking reaction. After the addition is completed, the reaction is carried out at 60°C for 3 hours to make chitosan and aldehyde-polyethylene glycol-acrylate fully react to form a stable modified chitosan structure.
[0045] Example 1 Preparation of modified activated carbon: weigh 5.0g activated carbon and 12g KMnO4 into a 500mL beaker, add 20mL10% H2SO4, then react at 35℃ for 1h, filter, rinse the filter residue with a large amount of deionized water until neutral, and dry at 100℃ to obtain activated activated carbon. Add 2.0g oxidized modified activated carbon and 4.0g 3-bromo-1-propylene to 80mL 60% ethanol solution, then stir and mix at 45℃ in the dark for 12h, filter, wash with anhydrous ethanol, and dry at 50℃ to obtain modified activated carbon.
[0046] Preparation of modified chitosan: dissolve 1 g of chitosan (molecular weight of 7000-8000, degree of deacylation: 75%) in 100 mL of deionized water, adjust the pH to 5-7, slowly add aldehyde-polyethylene glycol-acrylate (molecular weight of 1000-2000) under stirring, the mass ratio of aldehyde-polyethylene glycol-acrylate to chitosan is 1.5:1, react at 60°C for 3 h, cool, filter, and dry under reduced pressure at 50°C to obtain modified chitosan.
[0047] Preparation of sunscreen: Calculated by weight percentage, 60% of carbon black (particle size of 50 μm), 20% of zinc oxide (particle size of 300 μm) and 20% of titanium dioxide (particle size of 150 μm) are mixed, added to a mixer, and stirred evenly at an appropriate speed to ensure that each component is fully dispersed and mixed evenly to obtain a composite sunscreen.
[0048] Making food wrapping paper: S1, refining, refining coniferous wood pulp and hardwood wood pulp respectively, the beating degree of coniferous wood pulp after refining is 45-55°SR, and the beating degree of hardwood wood pulp is 35-45°SR, and then pulping is performed according to 65-75% coniferous wood pulp and 35-25% hardwood wood pulp to obtain mixed wood pulp; S2, adding 1.0% cationic starch, 0.5% wetting agent, and 1% composite sunscreen agent to the mixed wood pulp in sequence, and then stirring and mixing evenly; S3, adding water to the mixed wood pulp and diluting the mixed pulp to a concentration of 1.0%, using a fourdrinier paper machine to form the diluted pulp and obtain a wet paper sheet, the papermaking machine speed is 350 m / min; S4, dehydrating the formed wet paper sheet by suction under a vacuum condition of 0.07-0.8 MPa, drying the wet paper sheet at a temperature of 80-90° C. for 8-10 minutes, and finally calendering the wet paper sheet on a calender to obtain a base paper; S5, preparing a composite coating, taking 35 parts of polyethylene glycol and putting it into a heatable stirring device, heating it at 55°C to melt it, then sequentially adding 20 parts of acrylic resin emulsion, 10 parts of modified activated carbon, 10 parts of modified chitosan, and 1 part of initiator, stirring and mixing them evenly, then adding an appropriate amount of ethanol as a solvent according to actual use needs, adjusting the viscosity of the composite coating, obtaining a composite coating, applying the composite coating on both sides of the base paper to form a composite coating, and the coating amount of the composite coating is 5 gsm; S6, heating at 100-120° C. for 5-10 minutes to solidify the composite coating on the base paper, thereby obtaining the degradable food packaging paper.
[0049] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no sunscreen is added during the preparation of the food packaging paper in Comparative Example 1, and the remaining steps are the same as those in Example 1.
[0050] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the amount of acrylic resin emulsion added to the composite coating of Comparative Example 2 is 10 parts, and the remaining steps are the same as those of Example 1.
[0051] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that modified activated carbon is not added to the composite coating of Comparative Example 3, and an equal amount of acrylic resin emulsion is used instead, and the remaining steps are the same as those of Example 1.
[0052] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that modified chitosan is not added to the composite coating of Comparative Example 4, and an equal amount of acrylic resin emulsion is used instead, and the remaining steps are the same as those of Example 1.
[0053] The above-mentioned Example 1 and Comparative Examples 1-4 were tested for biodegradability, shading ability, tensile strength, oil resistance grade, water vapor permeability, and air permeability, respectively. Oil resistance performance test: TAPPI T 559cm-02, tensile strength: GB / T12914-2018, air permeability: GB / T458-2008, water vapor permeability: GB / T22921-2008, degradation performance (biodegradability): GB / T 39951-2021, shading rate test method: use an illuminometer combined with a shading plate test, place the illuminometer under the light source, and record the light intensity (I0) when there is no shading plate. Place the food packaging paper between the illuminometer and the light source, and record the light intensity (I) when there is a shading plate. Shading rate = (I0-I) / I0×100%. The higher the shading rate, the stronger the shading ability of the black paper.
[0054] The test results of Example 1 and Comparative Examples 1-4 are shown in the following table:
[0055] As for the light-shielding performance, the light-shielding rate of Example 1 reaches 92%, showing that it has good light-shielding ability. In contrast, the light-shielding rate of Comparative Example 1 (without adding light-shielding agent) is reduced to 60%. This change shows that the light-shielding agent (including carbon black, zinc oxide, titanium dioxide) plays a vital role in improving the light-shielding performance. The light-shielding rates of Comparative Examples 2 to 4 are all the same as that of Example 1, which is 92%, which further confirms that the light-shielding agent is the main factor determining the light-shielding performance. Therefore, it can be considered that the addition of the light-shielding agent plays a core role in enhancing the light-shielding effect of the packaging paper.
[0056] In terms of biodegradability, the biodegradability of the packaging paper in Example 1 is 95%, showing high degradability. The biodegradability of Comparative Example 1 (without sunscreen) is increased to 98%, indicating that the carbon black, zinc oxide and titanium dioxide in the sunscreen are non-degradable components. The biodegradability of Comparative Example 2 (reduced amount of acrylic resin) is increased to 97%, indicating that acrylic resin is a non-degradable material, while the biodegradability of Comparative Example 3 (without modified activated carbon) is reduced to 90%, which indicates that when the modified activated carbon is replaced by the non-degradable acrylic resin, the overall degradation performance is reduced. The biodegradability of Comparative Example 4 (without modified chitosan) is further reduced to 85%, which indicates that modified chitosan is a degradable material. After it is replaced by the non-degradable acrylic resin, its degradation performance is significantly reduced. Therefore, the addition of non-degradable materials (such as sunscreens and acrylic resins) will reduce the biodegradability of the packaging paper, while the introduction of degradable materials (such as modified chitosan) will help improve the degradation performance.
[0057] In terms of tensile strength, the tensile strength of the packaging paper of Example 1 is 4.70 KN / m, showing high mechanical properties. The tensile strength of Comparative Example 1 (without sunscreen) is reduced to 4.20 KN / m, which indicates that the sunscreen particles fill the fiber gaps and help to enhance the structural strength of the paper. The tensile strength of Comparative Example 2 (reduced amount of acrylic resin) is reduced to 4.30 KN / m, indicating that the reduction in the amount of acrylic resin as a film-forming component will lead to a decrease in the density of the coating, thereby affecting the strength of the paper. The tensile strength of Comparative Example 3 (without modified activated carbon) is reduced to 4.40 KN / m, indicating that the modified activated carbon enhances the bonding strength between the coating and the base paper through cross-linking. The tensile strength of Comparative Example 4 (without modified chitosan) is reduced to 4.50 KN / m, which indicates that the modified chitosan improves the mechanical properties of the paper through cross-linking and fiber reinforcement. Therefore, sunscreen, acrylic resin, modified activated carbon and modified chitosan all have a significant effect on the tensile strength of the paper.
[0058] In terms of oil resistance grade, the oil resistance grade of Example 1 is 12, showing good oil resistance performance. The oil resistance grade of Comparative Example 1 (without sunscreen) is reduced to 11, indicating that the lack of sunscreen filling in the base paper will reduce the oil resistance performance. The oil resistance grade of Comparative Example 2 (reduced acrylic resin dosage) is reduced to 10, indicating that the reduction in the amount of acrylic resin leads to a decrease in the density of the coating, thereby reducing the oil resistance performance. The oil resistance grade of Comparative Example 3 (without modified activated carbon) is reduced to 9, indicating that the modified activated carbon enhances the waterproof and oil-proof performance of the coating through cross-linking. The oil resistance grade of Comparative Example 4 (without modified chitosan) is reduced to 8, indicating that the modified chitosan significantly improves the oil resistance of the coating through cross-linking. Therefore, sunscreen, acrylic resin, modified activated carbon and modified chitosan are all important factors for improving the oil resistance of packaging paper.
[0059] In terms of air permeability and water vapor permeability, the packaging paper of Example 1 has an air permeability of 0.25 mL / min and a water vapor permeability of 550 g / m 2 ·24h, showing good barrier properties, the air permeability of comparative example 1 (without sunscreen) increased to 0.35 mL / min, and the water vapor transmission rate increased to 600 g / m 2 ·24h, indicating that the sunscreen particles filling the fiber gaps help enhance the barrier properties of paper. The air permeability of comparative example 2 (reduced acrylic resin dosage) increased to 0.30 mL / min, and the water vapor transmission rate increased to 590 g / m 2 ·24h, indicating that the reduction in the amount of acrylic resin leads to a decrease in the density of the coating, which in turn reduces the barrier performance. The air permeability of Comparative Example 3 (unmodified activated carbon) increased to 0.28 mL / min, and the water vapor transmission rate increased to 572 g / m 2·24h, indicating that the modified activated carbon enhanced the barrier properties of the coating through adsorption. The air permeability of comparative example 4 (unmodified chitosan) increased to 0.27 mL / min, and the water vapor transmission rate increased to 565 g / m 2 ·24h, indicating that the modified chitosan improved the barrier properties of the coating through cross-linking. Therefore, the sunscreen, acrylic resin, modified activated carbon and modified chitosan all had a significant effect on the air permeability and water vapor transmission rate.
[0060] In summary, sunscreen plays an important role in improving the sunscreen performance and enhancing the structural strength of paper, but its non-degradability will slightly reduce the biodegradability. Acrylic resin, as the main film-forming component, has a significant effect on the density, oil resistance and barrier properties of the coating. However, its non-degradability will reduce the overall degradation performance. Modified activated carbon and modified chitosan effectively improve the waterproof and oil-proof properties, barrier properties and mechanical properties of the coating through cross-linking and adsorption. At the same time, the degradability of modified chitosan helps to maintain a high biodegradability rate.
[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for making degradable food packaging paper, characterized in that: The following steps are involved: S1, refining, refining coniferous wood pulp and hardwood wood pulp respectively, the beating degree of coniferous wood pulp after refining is 45-55°SR, and the beating degree of hardwood wood pulp is 35-45°SR, and then pulping is performed according to 65-75% coniferous wood pulp and 35-25% hardwood wood pulp to obtain mixed wood pulp; S2, adding cationic starch, a wetting agent, and a composite sunscreen agent to the mixed wood pulp in sequence, and then stirring and mixing them evenly; S3, adding water to the mixed wood pulp and diluting the mixed pulp to a concentration of 0.8% to 1.0%, using a fourdrinier paper machine to form the diluted pulp and obtain a wet paper sheet, with a papermaking machine speed of 350 to 450 m / min; S4, dehydrating the formed wet paper sheet by suction under a vacuum condition of 0.07-0.8 MPa, drying the wet paper sheet at a temperature of 80-90° C. for 8-10 minutes, and finally calendering the wet paper sheet on a calender to obtain a base paper; S5, preparing a composite coating, coating the composite coating on both sides of the base paper to form a composite coating, wherein the coating amount of the composite coating is 2 to 5 gsm; S6, heating at 100-120° C. for 5-10 minutes to solidify the composite coating on the base paper, thereby obtaining the degradable food packaging paper.
2. The method for making a degradable food packaging paper according to claim 1, characterized in that: In step S2, the added amounts (absolute dry weight) of the cationic starch, wetting agent, and composite sunscreen are respectively: 1.0-1.2% cationic starch, 0.5-1.0% wetting agent, and 1-5% composite sunscreen.
3. The method for making a degradable food packaging paper according to claim 1, characterized in that: The cationic starch is selected from any one of tertiary amine alkyl cationic starch and quaternary ammonium alkyl cationic starch, and the wetting agent is selected from any one of urea-formaldehyde resin and polyamide polyepichlorohydrin resin.
4. The method for making a degradable food packaging paper according to claim 1, characterized in that: The composite sunscreen agent comprises the following raw materials: 60-70% carbon black, 20-15% zinc oxide, and 20-15% titanium dioxide. The particle size of the carbon black is 50-100 μm, the particle size of the zinc oxide is 150-400 μm, and the particle size of the titanium dioxide is 50-150 μm.
5. The method for making a degradable food packaging paper according to claim 1, characterized in that: In step S5, each component, measured by weight and fraction, includes the following raw materials: 10 to 15 parts of modified activated carbon, 10 to 15 parts of modified chitosan, 30 to 35 parts of acrylic resin emulsion, 10 to 15 parts of polyethylene glycol, and 1 to 5 parts of initiator.
6. The method for making a degradable food packaging paper according to claim 5, characterized in that: In step S5, the preparation method of the composite coating is: take 10 parts of polyethylene glycol and put it into a heatable stirring device, heat it at 55°C to dissolve it, and then add 35 parts of acrylic resin emulsion, 10 parts of modified activated carbon, 10 parts of modified chitosan, and 1 part of initiator in sequence, stir and mix evenly to obtain a composite coating.
7. The method for making a degradable food packaging paper according to claim 5, characterized in that: In step S5, the molecular weight of the acrylic resin emulsion is 4000-6000, the polyethylene glycol is PEG-4000 with a molecular weight of 3600-4400, and the initiator is selected from any one of benzoyl peroxide and tert-butyl peroxide 2-ethylhexyl.
8. The method for making a degradable food packaging paper according to claim 5, characterized in that: In step S5, the preparation method of the modified activated carbon is as follows: 5.0 g of activated carbon and 12 g of KMnO4 are weighed into a 500 mL beaker, and 20 mL of 10% H2SO4 is added, and then the mixture is reacted at 35°C for 1 h, filtered, and the filter residue is rinsed with a large amount of deionized water until it is neutral, and dried at 100°C to obtain activated activated carbon, 2.0 g of oxidized modified activated carbon and 4.0 g of 3-bromo-1-propylene are added to 80 mL of 60% ethanol solution, and then the mixture is stirred at 45°C in the dark for 12 h, filtered, washed with anhydrous ethanol, and dried at 50°C to obtain modified activated carbon.
9. The method for making a degradable food packaging paper according to claim 5, characterized in that: In step S5, the preparation method of the modified chitosan is: dissolve 1g of chitosan in 100mL of deionized water, adjust the pH to 5-7, slowly add aldehyde-polyethylene glycol-acrylate under stirring, react at 60°C for 3h, cool, filter, and dry under reduced pressure at 50°C to obtain modified chitosan.
10. The method for making a degradable food packaging paper according to claim 9, characterized in that: The mass ratio of the aldehyde-polyethylene glycol-acrylate to chitosan is (1-1.5):1, the molecular weight of the aldehyde-polyethylene glycol-acrylate is 1000-2000, the molecular weight of the chitosan is 7000-8000, and the degree of deacylation is 75%.
Citation Information
Patent Citations
Degradable food packaging paper and production process thereof
CN111074685A
Cited By
Preparation method of environment-friendly anti-aging packaging base paper and packaging base paper
CN121407417A
Preparation and treatment process for preservation of paper box and preservation paper box thereof
CN121719121A